L1 in L2: Indonesian towards English in Public Speaking Class - Surya Asra; Nizar Saputra; Irma Dewi Isda; Fadlia Fadlia; Winasti Rahma Diani (English Teaching and Linguistics Journal (ETLiJ), 2023)
Indonesian or Bahasa (L1) as a learner's first language is often used in English (L2) speaking lessons. This phenomenon often occurs even though teachers have informed them that using Indonesian during English-speaking skills classes is not permissible. Many reasons are suggested by experts why students use this first language. The most prominent reason is the student's lack of understanding of L2. However, this phenomenon still occurs in Public Speaking classes where students are already at the intermediate and advanced levels. In connection with this phenomenon, this study aims to find the main reasons students in the Public Speaking class use Indonesian in their English-speaking skills and what they think about using Indonesian in their English-speaking skills. A total of 50 students in two Public Speaking classes were observed and given questionnaires about their reasons and opinions for using Indonesian in speaking English skills. The results show that the highest reason students use L1 (Indonesian) in Public Speaking class is to process new and complex concepts. They argue that using Indonesian makes it easier for them to explain and understand the new concept.